Courage In Niki Caro’s Movie “Mulan (2020)” - Cibro, Nopa Ceria Wati; Murni, Sri Minda (Universitas Negeri Medan, 2023)
Principally this research attempts to find out 1) the types of courage by Mulan's character in Mulan (2020) movie. 2) how Mulan character’s courage showed in the movie. 3) factors that encouraged Mulan’s courage in the Movie. The research is done by descriptive qualitative research with the data source is the movie text script and scenes of Mulan (2020) movie. The instrument of collecting data is documentary sheet and images. The research results show that 1) There were 26 courages in the category types of courage. There are six courage categories, namely physical courage (15.39%), emotional courage (26.93%), intelectual courage (11.54%), social courage (15.39%), moral courage (23.08%), and spiritual courage (7.7%). 2) There are four the ways how the courage showed by Mulan character namely determination, self confidence, consistency, and optimism. 3) There are three factors that encouraged Mulan's character's namely altruism, self confident and situational demands, emotional and cognitive resources.